Chitin shape memory hemostatic sponge as well as preparation method and application thereof
By regulating the condensed structure and size of chitin fibers, and using hydrogen bond rearrangement, pure chitin shape memory hemostatic sponge material is prepared, which solves the problem of insufficient biosafety and degradability of existing chitin materials, and achieves excellent biocompatibility and efficient hemostatic properties of the material.
Patent Information
- Application Number
- CN202510272194.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
AI Technical Summary
The existing chitin hemostatic materials are used through chemical modification and crosslinking agents, which reduce the biosafety and degradability of the materials and limit their clinical applications.
By regulating the condensed structure and size of chitin fibers and using hydrogen bond rearrangement, pure chitin-shaped memory hemostatic sponge material is prepared without chemical modification or crosslinking agent.
It realizes excellent biosafety and degradability of chitin materials, and has good mechanical properties, liquid absorption properties and shape memory properties. It is suitable for hemostasis of deep, incompressible wounds and penetrating wounds, and can be used as a drug carrier for controlled release.
Smart Images

Figure CN119770706A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and particularly relates to a chitin shape memory hemostatic sponge and a preparation method and application thereof. Background Art
[0002] Uncontrolled bleeding is one of the leading causes of death worldwide, with 30% to 40% of traumatic deaths worldwide being caused by excessive blood loss. Bleeding during complex surgeries and trauma often leads to various complications, which increases the duration of surgery and the incidence of disease, so timely and effective hemostasis is very important. Existing hemostatic materials mainly come in the form of microspheres, sponges, hydrogels, gauze, and the like. Among them, hemostatic sponges have good water absorption, can quickly absorb blood and control bleeding, and have significant application advantages in hemostasis of deep, non-compressible wounds and penetrating wounds.
[0003] Chitosan is one of the most abundant biomacromolecules in the ocean and the only cationic polysaccharide in nature. Its unique chemical structure and composition endow it with good biological activities, such as antibacterial, healing, and immunomodulatory properties. Chitosan contains abundant positively charged amino groups, which can attract negatively charged red blood cells and protein aggregation, thereby promoting coagulation. It can also effectively promote platelet adhesion and aggregation, so it is particularly suitable as a hemostatic material. However, due to the large number of hydrogen bonds within and between chitosan molecules, the high crystallinity limits its solubility and dispersibility in neutral aqueous solutions, which greatly restricts its application.
[0004] Most of the existing chitosan hemostatic materials are chemically modified, such as deacetylation, carboxymethylation, hydroxyethylation, quaternization, etc., to enhance the water solubility of chitosan materials, and further add crosslinking agents to form chemical crosslinking structures on the basis of dissolution to enhance the mechanical properties and stability of the sponge. Chemical modification and the use of crosslinking agents reduce the biosafety and degradability of chitosan materials, thereby limiting the clinical application of the materials. Therefore, it is of great significance to develop a pure chitosan hemostatic material with good hemostasis and biocompatibility, without the need for chemical modification or the use of crosslinking agents, and with good liquid absorption performance, mechanical properties and biodegradability, which is of great significance for the clinical application of such materials. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a chitosan shape memory hemostatic sponge.
[0006] The chitosan shape memory hemostatic sponge material of the present invention has chitosan as the only component, has not been chemically modified, does not contain chemical cross-linking agents, and has a single component; it has excellent mechanical properties, hydrophilicity, and a multi-level interconnected pore structure, fast water / blood absorption speed, and good shape memory performance. It has the functions of rapid liquid absorption and shape recovery in water / blood, and has great application potential in the hemostasis of deep, non-compressible wounds and penetrating wounds. It can also be used as a carrier of local analgesics, anti-inflammatory drugs, etc. to achieve controlled release of drugs.
[0007] Another object of the present invention is to provide a method for preparing the chitosan shape memory hemostatic sponge.
[0008] The preparation method of the present invention can prepare a pure chitin shape memory hemostatic sponge material by regulating the condensed structure and size of chitin fibers and utilizing hydrogen bond rearrangement without chemically modifying chitin or using a crosslinking agent. The preparation method of the present invention has a simple process, is environmentally friendly, and has a single component. The obtained material has good biocompatibility and biodegradability. In the method of the present invention, the material obtained by hydrogen bond rearrangement fully exposes the functional groups in chitin, can effectively aggregate and attract platelets, red blood cells, and coagulation proteins, thereby accelerating hemostasis, and is suitable for hemostasis of massive bleeding, non-compressible wounds, and penetrating wounds. It can also be used as a carrier of local analgesics, anti-inflammatory drugs, etc. to achieve controlled release of drugs and further promote wound healing.
[0009] Another object of the present invention is to provide an application of the chitosan shape memory hemostatic sponge.
[0010] Another object of the present invention is to provide a drug-loaded chitin shape memory hemostatic sponge.
[0011] The purpose of the present invention is achieved through the following solutions: The first aspect is a chitosan shape memory hemostatic sponge, which is prepared from chitosan nanofibers by a solvent replacement method. The hemostatic sponge has a multi-level interconnected pore structure from nanometer to micrometer scale.
[0012] In the technical solution of the present invention, the solvent is water and ethanol solution.
[0013] In the technical solution of the present invention, the concentration of the ethanol solution can be 50-100%.
[0014] In the technical solution of the present invention, the average diameter of the chitin nanofibers is preferably 20-100 nm; the length is preferably 3-20 µm.
[0015] In the technical solution of the present invention, the sponge of the present invention is specifically obtained by dispersing chitosan nanofibers in water, adjusting the acidity, freezing, and then placing in an ethanol solution for solvent replacement.
[0016] In the technical solution of the present invention, the acidity adjustment refers to adjusting the pH to 1-5.
[0017] In the technical solution of the present invention, the water absorption rate of the chitosan shape memory hemostatic sponge can reach more than 9000%.
[0018] In the technical solution of the present invention, the compression modulus of the chitin shape memory hemostatic sponge after absorbing liquid is 0.9-3kPa.
[0019] In the technical solution of the present invention, the chitosan shape memory hemostatic sponge has a shape recovery time of less than 5 seconds after being compressed and absorbing liquid.
[0020] The second aspect is a method for preparing a chitosan shape memory hemostatic sponge, which specifically includes the following steps: freezing an acidic chitosan nanofiber dispersion into ice, then immersing it in ice ethanol for solvent replacement, and drying to obtain a chitosan shape memory hemostatic sponge.
[0021] In the technical solution of the present invention, the acidity refers to a pH of 1-5.
[0022] In the technical solution of the present invention, the acidity can be adjusted by acid solution, such as acetic acid, hydrochloric acid solution, etc.
[0023] In the technical solution of the present invention, the chitosan nanofiber dispersion can be obtained by dispersing chitosan nanofibers in water.
[0024] In the technical solution of the present invention, the concentration of chitosan nanofibers in the dispersion may be 0.3-1 wt %.
[0025] In the technical solution of the present invention, in the dispersion, the average diameter of the chitin nanofibers is preferably 20-100 nm; and the length is preferably 3-20 μm.
[0026] In the technical solution of the present invention, the dispersion liquid can be obtained by dispersing chitosan nanofibers in water by mechanical grinding, homogenization or ultrasound. Further, the speed of mechanical grinding is preferably greater than or equal to 1500rpm; the speed of homogenization is preferably greater than or equal to 8000rpm, and the homogenization time is preferably greater than or equal to 10min; the power of ultrasound is preferably greater than or equal to 45w; and the ultrasound time can be 3h.
[0027] In the technical solution of the present invention, the temperature of the icy ethanol is preferably -20°C or below.
[0028] In the technical solution of the present invention, the concentration of ethanol can be 50-100%.
[0029] In the technical solution of the present invention, the time for solvent replacement can be 24-48 hours.
[0030] In the technical solution of the present invention, drying can be achieved by conventional methods in the art such as freeze drying and supercritical drying.
[0031] The method of the present invention regulates the rearrangement of hydrogen bonds of chitin nanofibers by adjusting the acidity of the dispersion system, and then prepares a sponge material with functional groups in chitin exposed by solvent replacement. The sponge material can effectively aggregate and attract platelets, red blood cells and coagulation proteins, thereby accelerating hemostasis. In addition, there is a multi-level interconnected pore structure in the structure, and the water / blood absorption speed is fast. The sponge material is suitable for hemostasis of massive bleeding, non-compressible wounds and penetrating wounds. At the same time, it can also be used as a carrier of local analgesics, anti-inflammatory drugs, etc. to achieve controlled release of drugs and further promote wound healing.
[0032] In a third aspect, the present invention provides the use of the chitosan shape memory hemostatic sponge in the preparation of hemostatic and wound repair materials.
[0033] In a fourth aspect, the present invention provides the use of the chitosan shape memory hemostatic sponge as a carrier in loading drugs.
[0034] In a fifth aspect, the present invention provides a drug-loaded chitosan shape memory hemostatic sponge, which is obtained by the following method: immersing the chitosan shape memory hemostatic sponge in a solution containing the drug, and drying the solution to obtain the drug-loaded chitosan shape memory hemostatic sponge.
[0035] Compared with the prior art, the present invention has the following beneficial effects: (1) The chitosan shape memory hemostatic sponge of the present invention has a single component and is prepared only from chitosan nanofibers. It has not undergone any chemical modification and does not require the use of a cross-linking agent. It has excellent biosafety and degradability. At the same time, it has an excellent multi-level interconnected pore structure from nanometer to micrometer scale, exhibiting a high water absorption rate (>9000%) and a fast liquid absorption speed (shape recovery time <5 s). The compressed sponge has good shape memory performance. The compression modulus of the sponge after liquid absorption is 0.9-3 kPa, which can provide a suitable compression hemostatic effect for deep and narrow wounds, non-compressible wounds and penetrating wounds. (2) The preparation method of the chitosan shape memory hemostatic sponge of the present invention is simple and green. The target material can be prepared by conventional freezing and solvent replacement. It is environmentally friendly, has no emission of toxic and harmful substances, has mild conditions, and does not require harsh conditions such as high temperature and high pressure. It has obvious advantages and good industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 This is a photograph of the chitosan nanofiber dispersion in the preparation method of the present invention.
[0038] Figure 2 This is a TEM image of chitin nanofibers prepared by the method of the present invention.
[0039] Figure 3 This is an AFM image of chitin nanofibers prepared in the method of the present invention.
[0040] Figure 4 This is a diameter distribution diagram of chitin nanofibers in the preparation method of the present invention.
[0041] Figure 5 This is a schematic diagram of the reaction process of the chitosan shape memory hemostatic sponge of the present invention.
[0042] Figure 6 This is a scanning electron microscope image of the chitosan shape memory hemostatic sponge of the present invention.
[0043] Figure 7 This is a schematic diagram of the process of the chitosan shape memory hemostatic sponge of the present invention recovering its shape by absorbing water after being compressed.
[0044] Figure 8 This is a diagram showing the hemostatic effect of the chitosan shape memory hemostatic sponge of the present invention in a rat tail hemostasis experiment.
[0045] Fig. 9 This is a diagram showing the hemostatic effect of the chitosan shape memory hemostatic sponge of the present invention in a mouse liver puncture experiment.
[0046] All experimental samples contained three sets of parallel samples, and all data were expressed as mean standard deviation for statistical analysis, where: * p <0.05,** p <0.01,*** p <0.001. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can be obtained from commercial channels unless otherwise specified. The methods described are conventional methods unless otherwise specified. The amounts of each component are measured in parts by mass and parts by volume, g, mL. Example 1: Preparation of chitin shape memory hemostatic sponge
[0048] (1) 4 parts by mass of chitosan were added to 1000 parts by volume of water, acetic acid was added dropwise to the mixture to adjust the pH to 1.5, and the mixed suspension was poured into a grinder at a rotation speed of 1500 rpm or more and a grinding disc spacing of 0.25 μm to obtain a chitosan nanofiber dispersion. The morphology and size of the chitosan nanofibers in the dispersion were observed by visual inspection, AFM (atomic force microscope), TEM (transmission electron microscope), etc., and the size distribution of the nanofibers was statistically analyzed. The chitosan nanofiber dispersion of the present invention was uniform and stable, and the average size of the chitosan nanofibers was 60-80 nm in diameter and about 3-9 μm in length. Figure 1-Figure 4 The reaction diagram of the preparation process is shown in Figure 5 .
[0049] (2) The chitosan nanofiber dispersion was frozen at -80°C for 24 hours, and then placed in anhydrous ethanol at -20°C for 24 hours for low-temperature solvent replacement, and then placed in a -80°C refrigerator for 2 hours and freeze-dried to obtain a chitosan shape memory hemostatic sponge. The prepared sponge material was observed by scanning electron microscopy. Figure 6 It can be seen that the structure has a multi-level interconnected pore structure from nanometer to micrometer level, and the pores are abundant, so that the water absorption rate of the sponge can reach 9100%, and the shape recovery time is 3s. Example 2: Preparation of chitin shape memory hemostatic sponge
[0050] (1) 5 parts by mass of chitosan were added to 1000 parts by volume of water, acetic acid was added dropwise to the mixture to adjust the pH to 4, the dispersion was ground using a colloid mill at a speed of 12000 rpm to obtain a chitosan nanofiber dispersion, and the morphology and size of the chitosan nanofibers in the dispersion were observed by visual inspection, AFM (atomic force microscope), TEM (transmission electron microscope), etc., and the size distribution of the nanofibers was statistically analyzed. The chitosan nanofiber dispersion of the present invention was uniform and stable, and the average size of the chitosan nanofibers was 40-60 nm in diameter, which was similar to Example 1 and is not described in detail here.
[0051] (2) The chitosan nanofiber dispersion was frozen at -80°C for 24 h, and then placed in an ethanol solution (95%) at -20°C for 48 h for low-temperature solvent replacement. The chitosan shape memory hemostatic sponge was prepared using supercritical CO2. The supercritical CO2 pressure was 8 MPa, and the pressure holding time was 2 h. The water absorption rate of the obtained sponge reached 12600%, and the shape recovery time was 4 s. Example 3: Preparation of chitin shape memory hemostatic sponge
[0052] (1) 9 parts by mass of chitosan were added to 1000 parts by volume of water, acetic acid was added dropwise to the mixture to adjust the pH to 3, and the mixed suspension was poured into a grinder at a rotation speed of 1500 rpm or more and a grinding disc spacing of 0.25 μm to obtain a chitosan nanofiber dispersion. The morphology and size of the chitosan nanofibers in the dispersion were observed by visual inspection, AFM (atomic force microscope), TEM (transmission electron microscope), etc., and the size distribution of the nanofibers was statistically analyzed. The chitosan nanofiber dispersion of the present invention was uniform and stable, and the average size and length of the chitosan nanofibers were similar to those in Example 1, which are not described in detail here.
[0053] (2) The chitosan nanofiber dispersion was frozen at -80°C for 24 hours, then placed in anhydrous ethanol at -20°C for 24 hours for low-temperature solvent replacement, and then placed in a -80°C refrigerator for 2 hours and then freeze-dried to obtain a chitosan shape memory hemostatic sponge. The schematic diagram of the sponge recovering its shape after absorbing water / blood is shown in Figure 7 The water absorption rate of the sponge can reach 9000%, and the shape recovery time is 5s. Example 4: Evaluation of the hemostatic performance of the chitosan shape memory hemostatic sponge of the present invention using a rat tail hemostasis model
[0054] Healthy male SD rats were used, anesthetized by intraperitoneal injection of 10wt% chloral hydrate before surgery, and a 6cm long tail was cut to construct a bleeding model. Hemostatic materials were pressed on the wound, and the hemostatic time and blood loss were recorded. Gauze and gelatin sponge (commercially available) commonly used in clinical practice were selected as the control group, and the chitosan shape memory hemostatic sponge prepared in Example 1 was selected as the experimental group. Three parallel samples were set up in each group. The experimental results are shown in Figure 2. Figure 8 shown.
[0055] As can be seen from the figure, the amount of blood loss and the hemostasis time of the chitosan shape memory hemostatic sponge of the present invention in the rat tail hemostasis model are significantly better than those of the control group, wherein the hemostasis time of the gauze group of the control group is 826s, the gelatin sponge group is 203s, and the chitosan shape memory hemostatic sponge group is 72s, and the hemostasis time of the experimental group of the present invention is reduced by 91% and 65% compared with the gauze group and the gelatin sponge group, respectively; the amount of blood loss of the gauze group of the control group is 2.02g, the gelatin sponge group is 0.32g, and the chitosan shape memory hemostatic sponge group is 0.09g, and the amount of blood loss of the experimental group of the present invention is reduced by 96% and 72% compared with the gauze group and the gelatin sponge group, respectively. Example 5: Evaluation of the hemostatic performance of the chitosan shape memory hemostatic sponge of the present invention by liver puncture model
[0056] Male SD rats were used to construct a liver puncture model. The rats were anesthetized by intraperitoneal injection of 10wt% chloral hydrate before the operation, and the abdominal hair was shaved. The rats were then dissected and the liver was exposed. A circular puncture wound was constructed by a perforator. The wound surface was exposed for 5 seconds. After ensuring normal bleeding, the hemostatic material was filled into the wound surface. The bleeding time and blood loss were recorded every 10 seconds until the wound stopped bleeding. Gauze and gelatin sponge (commercially available) commonly used in clinical practice were selected as the control group, and the chitin shape memory hemostatic sponge prepared in Example 2 was selected as the experimental group. Three parallel samples were set in each group. The experimental results are shown in Figure 2. Fig. 9 The blood loss and hemostasis time of the chitosan shape memory hemostatic sponge in the liver puncture hemostasis model were significantly better than those of the control group, wherein the hemostasis time of the gauze group in the control group was 292s, the gelatin sponge group was 136s, and the experimental group of the present invention was 38s, and the hemostasis time was reduced by 87% and 72% compared with the gauze group and the gelatin sponge group, respectively; the blood loss of the gauze group in the control group was 1.62g, the gelatin sponge group was 0.30g, and the experimental group of the present invention was 0.10g, and the blood loss was reduced by 94% and 67% compared with the gauze group and the gelatin sponge group, respectively. Example 6: Preparation of chitosan shape memory hemostatic sponge loaded with curcumin
[0057] 1-3 parts by mass of curcumin is added to a 95% ethanol solution and stirred to dissolve for 12 hours to obtain a curcumin solution, and the chitosan hemostatic sponge prepared in Example 2 or 3 is placed in the above curcumin solution and soaked for 24 hours, taken out and placed in a -80°C refrigerator for 12 hours, and placed in a freeze dryer for freeze drying for 24 hours to obtain a chitosan hemostatic sponge loaded with curcumin that has anti-inflammatory, antioxidant, and wound repair-promoting properties.
[0058] The above embodiments illustrate that the chitosan shape memory hemostatic sponge of the present invention has excellent hydrophilicity and a multi-level interconnected pore structure, absorbs water / blood quickly, and has good shape memory performance. It has the functions of rapid liquid absorption and shape recovery in water / blood, and has great application potential in the hemostasis of deep, non-compressible wounds and penetrating wounds. It can also be used as a carrier of local analgesics, anti-inflammatory drugs, etc. to achieve controlled release of drugs.
Claims
1. A chitosan shape memory hemostatic sponge, characterized in that The hemostatic sponge is prepared from chitosan nanofibers by a solvent replacement method and has a multi-level interconnected pore structure from nanometer to micrometer scale.
2. The chitosan shape memory hemostatic sponge according to claim 1, characterized in that: The solvents are water and ethanol solution respectively.
3. The chitosan shape memory hemostatic sponge according to claim 1, characterized in that: The chitin nanofibers have an average diameter of 20-100 nm and a length of 3-20 μm.
4. A method for preparing a chitosan shape memory hemostatic sponge, characterized in that The following steps are involved: The acidic chitosan nanofiber dispersion is frozen into ice, then immersed in ice ethanol for solvent replacement, and dried to obtain a chitosan shape memory hemostatic sponge.
5. The preparation method according to claim 4, characterized in that: The acidic refers to a pH of 1-5.
6. The preparation method according to claim 4, characterized in that: The concentration of chitosan nanofibers in the dispersion is 0.3-1 wt %.
7. The preparation method according to claim 4, characterized in that: The temperature of the icy ethanol is -20°C or below.
8. Use of the chitosan shape memory hemostatic sponge according to any one of claims 1 to 3 in the preparation of hemostatic and wound repair materials.
9. Use of the chitosan shape memory hemostatic sponge according to any one of claims 1 to 3 as a carrier in loading drugs.
10. A drug-loaded chitin shape memory hemostatic sponge, characterized in that The method comprises the following steps: soaking the chitosan shape memory hemostatic sponge according to any one of claims 1 to 3 in a solution containing medicine, and drying the solution to obtain the medicine-loaded chitosan shape memory hemostatic sponge.
Citation Information
Patent Citations
Preparation method of chitin nanofiber composite collagen sponge dressing
CN105999372A
Porous material based on beta-chitin as well as preparation method and application of porous material
CN117624712A
Chitin nanofiber aerogel as well as preparation method and application thereof
CN117659493A
Nanofiber shape memory hemostatic sponge and preparation method thereof
CN118718068A